On some economic conditions of industrial development with special reference to the case of Ireland - Bastable, C. F. (Statistical and Social Inquiry Society of Ireland, 1884)
The improvement and expansion of the industrial powers of a country are naturally objects of considerable interest to all its inhabitants, but there does not appear to be any definite idea as to the laws which govern the industrial progress of a community. The aim of the present paper is briefly to consider some of the economic conditions which control the course of industrial development, as well as to see what practical methods would be in conformity with the requirements imposed by those conditions in the case of this country.
Read before the Society, 27 November 1883
Keywords: Industrial policy; Industrial development; Irish industry; Economic development; 314.15